Análisis urbano para la definición de componentes de diseño de espacio público en el dique Pambay, Puyo - Fuentes Barrionuevo, Angelly Belén (2025)
Considering that the city of Puyo is known as the "Gateway to the Amazon" due to its location in the central part of the Amazon region and its role as a connecting hub between the Sierra and Amazon regions, it functions as an urban and economic core of the area. This strategic position has led to the concentration of various infrastructures and activities within the urban fabric of the city. Consequently, the neighborhood of Ciudadela del Chofer includes a hydraulic and tourism-related facility known for its historical significance, referred to as the Pambay Dam. The archaeological richness of the Pastaza Valley is primarily known thanks to several Franco-Ecuadorian research projects: studies in collaboration with volcanologists in the Andean part of the river (Le Pennec et al. 2013; Saulieu et al. 2014), the “Zulay” project in the upper Pastaza, and archaeological surveys in the middle Pastaza. The most extensive excavations have taken place in the Puyo region, specifically in the upper Pastaza, with two notable sites: Pambay and Colina Moravia. Research indicates that pre-Columbian populations preferred to settle on the tops of small elevations that extend along the terraces of the Pambay River. Therefore, the oldest known culture in the Pastaza Valley is named Pambay and has been documented at two archaeological sites: Colina Moravia, near Shell, and Pambay, in the northern outskirts of Puyo. Evidence of these early settlements includes ceramics from the Pastaza basin, which remained unknown until recent years. The archaeological complexes and the regional chronology have been defined through recent studies (Saulieu 2006, 2013; Saulieu & Duche Hidalgo 2012; Rostain & Saulieu 2013; Rostain et al. 2014). Thus, tourism and cultural heritage are integral parts of this initiative. As one of the strategic projects outlined in the 2019 Development and Land Use Plan, the promotion and enhancement of Puyo as a tourist destination involves studying and revitalizing the Pambay River Dam, while preserving its historical and foundational legacy as a cultural and touristic landmark of the city.